Analisis Aktivitas Belajar Siswa dalam Pembelajaran Sejarah pada Pendidikan Menengah Atas - Fatmi Fauzani Duski (Tarikhuna: Journal of History and History Education, 2023)
The purpose of this research is to find out the various efforts in learning activities that have not been maximized as well as determine the causes of these efforts that have not been maximized. This research was conducted during the learning process took place in class xi. This study uses a qualitative research method with a qualitative descriptive approach. Data collection was carried out through observation of learning activities in learning activities including planning, implementation, evaluation and student activities. In addition, interviews were also conducted and supplemented by document studies. In order for the data in this study to be reliable, data triangulation was used. While the data analysis technique used is through the stages of data collection, data reduction, and drawing conclusions. The research objects were 38 class xi students and teachers in the field of history in that class. From the results of research in the field, it can be obtained that there are several learning activities studied in class xi, the learning activities carried out by the teacher can be said to be in accordance with the planning, implementation and evaluation of learning. Then the teacher's ability to create something new in history learning is quite good and student activities in listening, paying attention, asking questions, responding to questions, reading and doing exercises are in the sufficient category.